Aging with Cerebral Small Vessel Disease and Dizziness: The Importance of Undiagnosed Peripheral Vestibular Disorders - Cerchiai, Niccolò; Mancuso, Michelangelo; Navari, Elena; Giannini, Nicola; Casani, Augusto Pietro (Frontiers in Neurology, 2017)
Recent studies showed a link between cerebral Small Vessel White Matter Disease (SVD) and dizziness: patients whose dizziness cannot be explained by vestibular disease show severe SVD and gait abnormalities; however little is still known about how SVD can cause this symptom. The primary aim of this study is to examine the possible underlying causes of dizziness in neurovascular patients; this in order to assess whether treatable causes could be routinely disregarded. A secondary aim is to possibly define a central oculomotor pattern induced per se by SVD. This could help the diagnosis of SVD-related dizziness. In this single blind prospective study 60 patients referred to a neurovascular clinic because of dizziness and SVD on imaging were divided into a L-SVD and a H-SVD group (respectively low and high SVD burden), and then blindly examined with vestibulometric tests. In H-SVD group the percentage of unexplained dizziness reached 82.8%. There was a higher prevalence of peripheral vestibular abnormalities in the L-SVD patient group (51.6%) than in the H-SVD (17.2%; p=0.012). We found no differences in central oculomotor findings between the two groups. Although oculomotricity does not show any consistent pattern, a severe SVD can directly represent a cause of dizziness. However, a patient with mild SVD is more likely to suffer by a peripheral vestibular disorder. Therefore, given the high incidence of vestibular disease in neurovascular or geriatric clinics, clinicians should be cautious when ascribing dizziness solely to the presence of SVD as easily treatable peripheral vestibular causes may be missed.